Combination lenalidomide‐rituximab immunotherapy activates anti‐tumour immunity and induces tumour cell death by complementary mechanisms of action in follicular lymphoma. (14th February 2019) - Chiu, Hsiling; Trisal, Preeti; Bjorklund, Chad; Carrancio, Soraya; Toraño, Estela G.; Guarinos, Carla; Papazoglou, Despoina; Hagner, Patrick R.; Beldi‐Ferchiou, Asma; Tarte, Karin; Delfau‐Larue, Marie‐Hélène; Morschhauser, Franck; et al.
Summary: Chemotherapy plus rituximab has been the mainstay of treatment for follicular lymphoma (FL) for two decades but is associated with immunosuppression and relapse. In phase 2 studies, lenalidomide combined with rituximab (R 2 ) has shown clinical synergy in front‐line and relapsed/refractory FL. Here, we show that lenalidomide reactivated dysfunctional T and Natural Killer (NK) cells ex vivo from FL patients by enhancing proliferative capacity and T‐helper cell type 1 (Th1) cytokine release. In combination with rituximab, lenalidomide improved antibody‐dependent cellular cytotoxicity in sensitive and chemo‐resistant FL cells, via a cereblon‐dependent mechanism. While single‐agent lenalidomide and rituximab increased formation of lytic NK cell immunological synapses with primary FL tumour cells, the combination was superior and correlated with enhanced cytotoxicity. Immunophenotyping of FL patient samples from a phase 3 trial revealed that R 2 treatment increased circulating T‐ and NK‐cell counts, while R‐chemotherapy was associated with reduced cell numbers. Finally, using an in vitro model of myeloid differentiation, we demonstrated that lenalidomide caused a reversible arrest in neutrophil maturation that was distinct from a cytotoxic chemotherapeutic agent, which may help explain the lower rates of neutropenia observed with R 2 versus R‐chemotherapy. Taken together, we believe these data support a paradigm shift in the treatment of FL – moving from combination immunochemotherapy to chemotherapy‐free immunotherapy.